Enhancing Blood Donation Intentions Using the Train-the-Trainer ( TTT ) Model: A Field Trial Study - Mirrezaie 1*, Seyed Mohammad; Jamali 2, Mostafa; Hajibeigi 2, Bashir; Golmakani 3, Mohammad Mehdi; Sadegh 2, Hossein; Abbasian 2, Ali; Mirzamoradi 4, Masoumeh (Shahroud Journal of Medical Sciences, 2016)
Background: In Iran, despite various attempts to increase recruitment of female blood donors, women make up less than 10% of blood donors.Methods: The purpose of the study was to evaluate the effect of face-toface education via the Train-the-Trainer (TTT) model on people’s willingness to donate blood, especially women. A field trial study was designed based on a face-to-face educational plan for a population in 22 municipal regions of Tehran, the capital of Iran. The periods from March 2011 to February 2011 and from March 2010 to February 2010 were named as trial 2 and trial 1, respectively.Results: Total number of volunteers in trial 2 was 9,178 cases, including 2,785 females and 6,393 males, compared with 4,074 cases, including 454 females and 3,620 males, in trial 1. Female/male ratios in trials 1 and 2 were 0.13 and 0.44, respectively (p<0.001). Deferred donors made up 24% (981/4074) of 4,074 in trial 1, and of the 9,178 donors in trial 2, 29% (2693/9178) were deferred (p<0.001). The most common cause in trial 1 was erythrocytosis, 20%, and in trial 2 was anemia, 21.5%.Conclusions: Overall, face-to-face education is an appropriate method for enhancing safe blood donor motivation and recruitment.